The Scalp Time-Varying Networks of N170: Reference, Latency, and Information Flow - Tian, Yin; Xu, Wei; Zhang, Huiling; Tam, Kin Y.; Zhang, Haiyong; Yang, Li; Li, Zhangyong; Pang, Yu (Frontiers in Neuroscience, 2018)
Using the scalp time-varying network method, the present study is the first to investigate the temporal influence of the reference on N170, a negative event-related potential component (ERP) appeared about 170ms that is elicited by facial recognition, in the network levels. Two kinds of scalp electroencephalogram(EEG) references, namely, AR (average of all recording channels) and REST (reference electrode standardization technique), were comparatively investigated via the time-varying processing of N170. Results showed that the latency and amplitude of N170 were significantly different between REST and AR, with the former being earlier and smaller. In particular, the information flow from right temporal-parietal P8 to left P7 in the time-varying network was earlier in REST than that in AR, and this phenomenon was reproduced by simulation, in which the performance of REST was closer to the true case at source level. These findings indicate that reference plays a crucial role in ERP data interpretation, and importantly, the newly developed approximate zero-reference REST would be a superior choice for precise evaluation of the scalp spatio-temporal changes relating to various cognitive events.